2009
DOI: 10.1021/bi900196c
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of Vertebrate H2A.Z and Its Effect on the Structure of the Nucleosome

Abstract: Purified histone H2A.Z from chicken erythrocytes and a sodium butyrate-treated chicken erythroleukemic cell line was used as a model system to identify the acetylation sites (K4, K7, K11, K13, and K15) and quantify their distribution in this vertebrate histone variant. To understand the role played by acetylation in the modulation of the H2A.Z nucleosome core particle (NCP) stability and conformation, an extensive analysis was conducted on NCPs reconstituted from acetylated forms of histones, including H2A.Z a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 58 publications
3
103
1
Order By: Relevance
“…This distinction could be due to a divergence in H2A.Z properties between yeast and C. elegans (Zlatanova and Thakar 2008). It is also possible that the H2A.Z-containing nucleosomes used for analysis in this study (measured by Ho et al 2014) were comprised of the particularly stable, homotypic type of H2A.Z nucleosomes (Ishibashi et al 2009). …”
Section: Mnase-resistant Nucleosomes Tend To Be In Gene Bodies and Comentioning
confidence: 98%
“…This distinction could be due to a divergence in H2A.Z properties between yeast and C. elegans (Zlatanova and Thakar 2008). It is also possible that the H2A.Z-containing nucleosomes used for analysis in this study (measured by Ho et al 2014) were comprised of the particularly stable, homotypic type of H2A.Z nucleosomes (Ishibashi et al 2009). …”
Section: Mnase-resistant Nucleosomes Tend To Be In Gene Bodies and Comentioning
confidence: 98%
“…Previous studies have proposed that H2A.Z functions as a structural component in the heterochromatin context, where the morestable hypoacetylated homotypic (H2A.Z-H2A.Z) nucleosomes might influence the folding of the chromatin fiber and facilitate the formation of secondary structures with increased compaction (Fan et al, 2002;Fan et al, 2004;Ishibashi et al, 2009;Suto et al, 2000). This is supported by a series of observations in yeast, where H2A.Z mostly functions as a negative regulator of transcription in the case of heterochromatic regions (Buchanan et al, 2009;Dhillon and Kamakaka, 2000;Hou et al, 2010).…”
Section: Different Dynamics Of H2a and H2az Deposition At Phcmentioning
confidence: 99%
“…In vitro studies aimed at investigating the structural impact of the incorporation of H2A.Z on nucleosome dynamics have generated contradictory observations with respect to its stability. 68,69 Differences in the methodologies used in these studies may explain at least part of the discrepancies observed. A number of these studies were conducted with nucleosomes assembled in vitro using bacterially purified recombinant histones.…”
Section: H2az and Dna Methylationmentioning
confidence: 99%
“…A number of these studies were conducted with nucleosomes assembled in vitro using bacterially purified recombinant histones. [68][69][70][71] These artificial nucleosomes were shown to have different characteristics when compared to native nucleosomes. 72 It appears that in vitro assembly of histones does not perfectly mimic the native folding of histones and/or that chaperone-assisted folding of nucleosomes is important for proper nucleosome assembly.…”
Section: H2az and Dna Methylationmentioning
confidence: 99%